Use of shell-shape to discriminate between Brachidontes rodriguezii and Brachidontes purpuratus species (Mytilidae) in the transition zone of their distributions (south-western Atlantic) - Van der Molena, Silvina (2013)
Fil: Van der Molena, Silvina. Centro Nacional Patagónico CENPAT. Puerto Madryn; Argentina